Achieving efficient violet-light-excited blue phosphors by nitridation for violet-chip-based full-spectrum lighting. Issue 8 (24th March 2023) - Dou, Chao; Zhao, Fangyi; Liu, Shengqiang; Song, Zhen; Liu, Quanlin
Abstract : By partially introducing N 3− into a matrix, a new efficient and thermally stable Ba0.697 Al10.914 O15.732 N1.0 :0.16Eu 2+ blue phosphor has been synthesized, which can better match with violet chips for full-spectrum lighting. Abstract : With the pursuit of healthy lighting, full-spectrum white light-emitting diodes (WLEDs) fabricated with violet chips and tri-color phosphors have been put forward. However, the excitation bands of most reported blue phosphors are located in the ultraviolet (UV) region, which hinders the development of full-spectrum lighting. In this work, by partially introducing N 3− into a matrix, a series of Ba0.697 Al10.914 O17.232-3 y /2 N y :0.16Eu 2+ (BAON y :Eu) blue phosphors with red-shifted photoluminescence excitation (PLE) spectra were synthesized. Under the excitation of 400 nm violet light, the internal/external quantum efficiency (IQE/EQE) values of the optimal sample BAON1.0 :Eu were calculated to be 80%/52%, while the retained integrated emission intensity at 150 °C can be 95% of that at room temperature. The WLED device fabricated by coating BAON1.0 :Eu and other commercial phosphors on a violet chip achieved an ultra-high color rendering index ( R a = 95.4). These results indicate that our synthesized BAON1.0 :Eu can be an excellent candidate blue phosphor for full-spectrum WLED lighting.